Persulfidation-based Modification of Cysteine Desulfhydrase and the NADPH Oxidase RBOHD Controls Guard Cell Abscisic Acid Signaling. Issue 4 (5th February 2020) - Shen, Jie; Zhang, Jing; Zhou, Mingjian; Zhou, Heng; Cui, Beimi; Gotor, Cecilia; Romero, Luis C.; Fu, Ling; Yang, Jing; Foyer, Christine Helen; Pan, Qiaona; Shen, Wenbiao; et al.
Abstract : A persulfidation-based reversible post-translational modification of Cys desulfhydrase and NADPH oxidase RBOHD fine-tunes guard cell ABA signaling. Abstract: Hydrogen sulfide (H2 S) is a gaseous signaling molecule that regulates diverse cellular signaling pathways through persulfidation, which involves the post-translational modification of specific Cys residues to form persulfides. However, the mechanisms that underlie this important redox-based modification remain poorly understood in higher plants. We have, therefore, analyzed how protein persulfidation acts as a specific and reversible signaling mechanism during the abscisic acid (ABA) response in Arabidopsis ( Arabidopsis thaliana ). Here we show that ABA stimulates the persulfidation of l -CYSTEINE DESULFHYDRASE1, an important endogenous H2 S enzyme, at Cys44 and Cys205 in a redox-dependent manner. Moreover, sustainable H2 S accumulation drives persulfidation of the NADPH oxidase RESPIRATORY BURST OXIDASE HOMOLOG PROTEIN D (RBOHD) at Cys825 and Cys890, enhancing its ability to produce reactive oxygen species. Physiologically, s -persulfidation-induced RBOHD activity is relevant to ABA-induced stomatal closure. Together, these processes form a negative feedback loop that fine-tunes guard cell redox homeostasis and ABA signaling. These findings not only expand our current knowledge of H2 S function in the context of guard cell ABA signaling, but also demonstrate the presence of a rapid signal integration mechanism involving specific and reversible redox-based post-translational modifications that occur in response to changing environmental conditions.